Practicals in science education: a study of the theoretical bases, rationale and implementation of practicals in junior secondary science education - Bradley, Duncan (Curtin University, 2005)
This study explores the issues involved in the theoretical bases, rationale and implementation of practical work in junior secondary science programs. The part that practical work has played in science education, both internationally and in Australia, is reviewed. Links are made between statements made by science educators more than 200 years ago to those made by modern day researchers into science teaching and learning. The study draws together the research traditions of the philosophy of science, science curriculum development, learning environments, and educational psychology. The researcher has carried out a multi-stage field study using both qualitative and quantitative methods to achieve the objectives of the study. Developments in the philosophy of science as they impinge on science education are reviewed. Science practicals are defined for the purposes of this study and a new Theoretical Model for Science Practicals is proposed. The model enables the description and statement of purpose of eight types of science practicals. The target population of the study is Australian science teachers and students. The model provides a theoretical basis for the development of the survey instrument, Science Practicals Inventory (SPI), to investigate students’ perceptions of the use of practicals in science learning. The eight types of practicals described in the model were used as the scales for the SPI. Qualitative data collected during separate group interviews of science teachers and students supported the development of the SPI together with quantitative data from three pilot studies. The SPI was validated using samples of high school students from Tasmania and Western Australia.Using statistical procedures involving factor analyses, alpha reliability, discriminant validity, and ANOVA, a valid, reliable, efficient, eight scale, 50 item instrument has been developed. Analysis of the quantitative and qualitative data in this study enabled issues involved in the theoretical bases, rationale and implementation of practical work in junior secondary science programs to be clarified and better understood. The results of this study include implications for science curricula and recommendations for further research and are generalizable to science teachers and students in Australia. The SPI is available for further application in action research, science program evaluation, science teacher professional learning and science program renewal.